High Thermoelectric Efficiency of n‐type PbS. Issue 4 (7th November 2012) - Wang, Heng; Schechtel, Eugen; Pei, Yanzhong; Snyder, G. Jeffrey
Abstract PbS shares several features with the other lead chalcogenides PbX (X: Te, Se), which are good thermoelectric materials. PbS has a potential advantage in that it is quite earth abundant and inexpensive. In this work we tune the transport properties in n‐type, single‐phase polycrystalline PbS1‐xClx (x ≤ 0.008) with different carrier densities. Lead chloride provides a nearly 100% efficient doping control up to 1.2 × 1020 cm−3. The maximum zT achieved at 850 K is 0.7 with a predicted zT ∼ 1 at 1000 K. This is about twice as high as what was previously reported (∼0.4) for binary PbS. Compared with the other lead chalcogenides the higher effective mass and higher lattice thermal conductivity makes binary PbS an inferior thermoelectric material. However this study also predicts greater potential of zT improvement in PbS by material engineering such as alloying or nanostructuring compared to PbSe or PbTe. Considering their abundance and low cost, PbS based materials are quite competitive among the lead chalcogenides for thermoelectric applications.